Paediatric medicine issues and gaps from healthcare workers point of view: survey results and a narrative review from the global accelerator for paediatric formulations project - Barbieri, Elisa; Minotti, Chiara; Cavagnis, Sara; Giaquinto, Carlo; Cappello, Bernadette; Penazzato, Martina; Lallemant, Marc (Frontiers in Pharmacology, 2023)
The WHO Model List of Essential Medicines for Children (EMLc) has not been systematically revised in the last few years. We conducted a survey addressed to healthcare professionals prescribing, preparing, or administering medicines to children and a narrative review to identify problematic paediatric formulations or missing medicines in all therapeutic fields to inform the review of the EMLc in 2023. A total of 285 physicians (63%), 28 nurses (6%) and 142 pharmacists (31%), mostly working in the hospital setting, reported at least one problematic medicine. 290 medicines were reported as missing (completely or the child-appropriate formulation). The top three most mentioned were ciprofloxacin together with phenobarbital and omeprazole. 387 medicines were reported as problematic (34% were oral liquid formulations, 34% tablets, 18% parenteral preparations. Mostly of the products were antibacterials (27%), cardiovascular medicines (11%) and antivirals (11%). The obtained responses show the perspective of healthcare workers working around the world, particularly in the European region (25%), in the African region (24%), and in the Region of the Americas (19%), with limited representation from Northern Africa and the Middle East. Our results need to be analysed with the outputs of other ongoing works before specific products can enter the WHO-hosted Global Accelerator for Paediatric formulations network prioritisation process. Efforts to develop appropriate formulations for children should be accelerated so that the uncertainties associated with off-label drug preparation and use are minimised, and therapeutic benefits are optimised.